Endothelin receptor antagonist in chronic kidney disease - Choopun, Kitjapong; Wongpraphairot, Suwikran (Journal of the Nephrology Society of Thailand, 2022)
Endothelin-1 is the most potent vasoconstrictor that regulates renal perfusion, controls glomerular arteriolar tone and stimulates inflammation and fibrosis leading to progressive chronic kidney disease. Endothelin-1 is derived mainly from endothelial cells and is synthesized by endothelin converting enzymes. Endothelin-1 activates through both endothelin A and endothelin B receptors. When activated through the endothelin A receptor, it results in vasculature vasoconstriction, mesangium proliferation, extracellular matrix accumulation, podocyte injury, proteinuria, tubulointerstitial fibrosis, inflammation and cell infiltration. In contrast, the outcomes of binding through the endothelin B receptor are vasodilation, decreased cellular proliferation and decreased inflammatory cells. Clinical studies report endothelin A-selective blocker has been demonstrated to reduce proteinuria, glomerular pressure and arterial stiffness in non-diabetic and diabetic kidney disease, particularly among patients taking angiotensin converting enzyme inhibitor or angiotensin receptor blocker at maximum tolerated dose. In conclusion, endothelin receptor antagonists represent promising drugs to delay progression in chronic kidney disease. Adverse effects such as fluid retention must be considered. This review article summarizes the pathogenesis of endothelins in chronic kidney disease and clinical trials of endothelin receptor antagonists.